High‐Performance Asymmetric Li‐Ion Pseudocapacitors Based on Pyroprotein Nanowebs. Issue 8 (31st May 2017) - Cho, Se Youn; Kim, Na Rae; Jin, Hyoung‐Joon; Yun, Young Soo
Abstract: Modern industrial technologies require high power and energy storage devices with long‐term cycling stabilities; the electrochemical performances of these devices are mainly dependent on the active electrode materials and their energy storage mechanisms. In this study, nanoweb‐structured pyroprotein nanofibers (NW‐PNFs) were prepared from electrospun silk protein by pyrolysis. NW‐PNFs have an open macroporous structure formed by entangled nanofibers and numerous micropores originating from the amorphous pseudographitic microstructure of the nanofibers. In addition, they possessed a large number of heteroatoms (10.3 at. % oxygen and 5.2 at. % nitrogen). These material properties led to superior Li‐ion storage performances with high reversible capacity of about 1, 050 mA h g −1 at 0.5 A g −1 and great cycling performance over 3, 000 cycles. In particular, NW‐PNFs exhibited high rate capability even at the specific current of 50 A g −1, at which the high specific capacity of circa 400 mA h g −1 was achieved. Furthermore, asymmetric Li‐ion storage devices based on NW‐PNFs showed feasible electrochemical performances with a maximum specific energy of 235.7 Wh kg −1 at 188.6 W kg −1 and maximum power of 21, 220 W kg −1 at 69.6 Wh kg −1 . Abstract : A tangled web : Nanoweb‐structured pyroprotein nanofibers (NW‐PNFs) were prepared from electrospun silk protein by pyrolysis. These materials show high energy and power performances with long‐lasting cycle life.